ANALISIS PERBANDINGAN KINERJA REKSA DANA KONVENSIONAL DAN REKSA DANA SYARIAH MENGGUNAKAN MODEL PENGUKURAN SHARPE, TREYNOR, REWARD TO MARKET RISK DAN REWARD TO DIVERSIFICATION - , Adi Hari Susanto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In investing, mutual fund is one way to diversify investments. Based on the principle that was followed, a mutual fund that is divided into two conventional mutual funds and Islamic mutual funds. In terms of return, Islamic mutual funds are still smaller than conventional mutual funds. But they still can provide benefits that exceed the gains from interest rate deposits. Mutual fund both conventional and sharia, successfully attracted many investors because of several advantages it has. The purpose of this study is to provide information to investors in choosing a mutual fund as an investment option by looking at the performance of mutual funds based on the degree of variability, the rate and magnitude volatibilitas diversification achieved. The research data used in this study is secondary data obtained from PT Infovesta Utama, Bapepam and Bank Indonesia. Samples taken in this study of 30 (thirty) mutual funds that are still active by October 31, 2011 both conventional and Islamic to the same sub-category of stock, mixed and fixed income. To analyze the return on mutual funds both conventional and Islamic, this study used four models of measuring that are Sharpe (RVAR) index, Treynor (RVOL) index, Reward to Market Risk (RMAR) index and Reward to Diversification (RDIV) index. Based on performance appraisal of equity and mixed mutual funds as measured by Sharpe index, Treynor index, Reward to Market Risk index and Reward to Diversification index during the period January 1, 2008 until October 31, 2011, the performance of conventional mutual funds are better than the performance of Islamic mutual funds. While the performance of fixed income mutual funds as measured by the Sharpe index, Treynor index, Reward to Market Risk index and Reward to Diversification index during the same period, the performance of Islamic mutual funds are better than the performance of conventional mutual funds.